Effect of Users Perception of Library Resources on Library Use: A Case Study of Faculty Libraries in the University of Ibadan - Enidiok, Mary Sunday; Bassey, Akpan Ben; Babatunde, Asiat Adunola (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
This study was undertaken to determine the effect of users’ perception of library resources on library use; using University of Ibadan faculty library as a case study. The overall purpose of the study was to determine the effects of users’ perception of library resources on library use and to investigate the role of library resources in meeting the information needs of the users. A simple random sampling technique was adopted in selecting 200 registered faculty library users as respondents for the study. A questionnaire instrument was used for data collection. Descriptive statistics were used to analyze each of the variables on the questionnaire and results were presented in frequency tables and percentages to show occurrences and events of each variable. Findings indicate that students in the University of Ibadan have a negative perception of the library resources because faculty libraries do not possess abundant resources for students use, couple with the poor accessibility of the resources to the students. The study recommends that the University authority should through the acquisition librarian, acquire specific library resources needed by the students and faculty members, in all formats.